Prior knowledge and other individual differences in the development of accuracy over the time-course of a pre-test/treatment/post-test study of instructed second language acquisition. Issue 2 (16th October 2020) - Lee, James F.; Doherty, Stephen
Abstract : Time-course data are temporal data that can be explored statically as an outcome measure of accuracy or dynamically from evolutionary and developmental perspectives. The present study examines the development and evolution of accuracy throughout the time-course of a pre-test/treatment/post-test study of instructed second language acquisition. The treatment is processing instruction (PI), which has a long history of positive results. PI research has overwhelmingly compared pre-test with post-test accuracy scores. The present study provides a fine-grained analysis as accuracy evolved and developed sentence by sentence. We analyse two sentence types: baseline active sentences and the target of instruction, passive sentences. Participants were divided into two groups, higher/lower prior knowledge, based on their pre-test scores processing passive sentences. Typically, PI research excludes higher prior knowledge participants, but here they are a comparison group. Our base measurement of development is an accuracy trend, defined as at least three correct answers in a row. We found that the number and length of accuracy trends increased over the time-course of the study and are affected by both sentence type and prior knowledge. The higher prior knowledge group always seems to have the advantage. Both prior knowledge groups benefit from instruction, but in different ways. We also found individual differences within the lower prior knowledge group: some participants benefited a great deal from instruction, some very little, and for some their accuracy with the baseline active sentences was temporarily destabilised.